A Comparison of Motor Recovery After Spinal Anesthesia with and Without Fentanyl-Morphine Adjuvants - Ardi Nugraha; Magenda Bisma Yudha; Septian Mixrova Sebayang (Jurnal Kegawatdaruratan Medis Indonesia, 2026)
Spinal anesthesia is a commonly used regional anesthesia technique in various surgical procedures. One important parameter following spinal anesthesia is motor block recovery. Shorter motor recovery duration may benefit patients by reducing side effects and enabling earlier mobilization. This study aimed to compare motor recovery time between spinal anesthesia without adjuvant and spinal anesthesia combined with fentanyl 25 μg and morphine 100 μg. This comparative analytic study used an observational approach with purposive sampling. A total of 84 respondents were divided into two groups: 42 patients received 0.5% bupivacaine 12.5 mg without adjuvant, and 42 patients received 0.5% bupivacaine 10 mg combined with fentanyl 25 μg and morphine 100 μg. Motor recovery time was measured from intrathecal injection to the achievement of a Bromage Score of 0. The mean motor recovery time in the non-adjuvant group was 164.95 ± 24.685 minutes, while the adjuvant group showed a shorter recovery time of 116.90 ± 17.177 minutes. Mann–Whitney analysis demonstrated a statistically significant difference between the two groups (p < 0.001). Spinal anesthesia combined with fentanyl and morphine was associated with faster motor recovery compared with spinal anesthesia without adjuvant.